What constitutes a new party? The lack of a standard operationalization and the way forward - Rahat, Gideon (Frontiers in Political Science, 2025)
This mini-review examines scholars' responses to the question, “What constitutes a new party?” It proposes a path out of a situation in which there is no one standard answer to this question, or even a dominant answer. The absence of a standard or dominant answer creates an interesting setting for theoretical and methodological creativity. At the same time, the situation is problematic: with no agreed answer, large n studies that differ in how they define and operationalize party newness are not comparable. And because political parties are central actors in democratic politics, this situation negatively affects comparative politics research. An agreed answer (or answers) is especially critical for studies that analyze stability, continuity, and change of party organizations, party systems, and the political system as a whole. This article reviews the approaches to party newness and identifies their main features. No one approach seems to be substantially preferable to the others. Thus, the way forward is to establish a database that will include the data already produced on party newness. Such a database will enable comparison of the different codifications and measurements and systematically examine their similarities and differences.